A big data based data storage systems for rock burst experiment. (1st January 2013) - Zhang, Yu; Bai, Yan-Ping; Zhu, Dong-Feng; Lv, Zhao-Yong
State Key Laboratory for GeoMechanics and Deep Underground Engineering, Deep- Lab for short, has been committed to the study of rock burst. Deep-Lab accumulated a large number of rock-burst data. With the deepening of the research progress, massive-data dilemma, artificial-management-data dilemma and experimental-data-analysis dilemma have become three big problems of rock burst. These dilemmas restrict the development of rock burst research technologies. This article takes big data in rock burst experiment as research objects and innovatively introduces big data technology into rock burst. Digital features of rock-burst experimental data were extracted. On this basis, a big data based data storage systems for rock burst experiment, BDSS for short, was designed and built. Then an integrated rock burst experimental platform was constructed. Experiments show that, BDSS solves three dilemmas of rock burst, and realises the distributed storage system of data. BDSS also realises dynamic and efficient load of rock-burst big data, and its efficient query under complication conditions.